Dispatcher-assisted conventional cardiopulmonary resuscitation and outcomes for paediatric out-of-hospital cardiac arrests. (March 2022) - Goto, Yoshikazu; Funada, Akira; Maeda, Tetsuo; Goto, Yumiko
Abstract: Aim: As asphyxial cardiac arrest is more common than cardiac arrest from a primary cardiac event in paediatric cardiac arrest, effective ventilation is important during paediatric cardiopulmonary resuscitation (CPR). We aimed to determine optimal dispatcher-assisted CPR instructions for bystanders after paediatric out-of-hospital cardiac arrest (OHCA). Methods: We analysed the records of 8172 children who received bystander dispatcher-assisted CPR. Data were obtained from an All-Japan Utstein-style registry from 2005 to 2017. Patients were divided into conventional CPR and compression-only CPR groups. The primary study endpoint was 1-month neurologically intact survival, defined as a Cerebral Performance Category score of 1 or 2 (CPC 1–2). Results: The 1-month CPC 1–2 rate was significantly higher in the dispatcher-assisted conventional CPR group than in the dispatcher-assisted compression-only CPR group (before propensity score matching, 5.7% [175/3077] vs. 3.1% [160/5095], p < 0.0001, adjusted odds ratio 2.48, 95% confidence interval 1.19–3.22; after propensity score matching, 6.0% [156/2618] vs. 2.6% [69/2618], p < 0.0001, adjusted odds ratio 2.42, 95% confidence interval 1.76–3.32). In most subgroup analyses after matching, dispatcher-assisted conventional CPR had a higher CPC 1–2 rate than dispatcher-assisted compression-only CPR; however, CPC 1–2 rates were similar between the two groups for patients with an initial shockable rhythm, those with total prehospital CPR time ≥ 20 min, those receiving public access defibrillation, advanced airway management, or adrenaline administration. Conclusion: Within the limitations of this retrospective observational study, dispatcher-assisted conventional CPR was preferable to dispatcher-assisted compression-only CPR as optimal CPR instructions for coaching callers to perform bystander CPR.